Development of a high-quality rare earth oxide modified resin-based brake material. (2nd January 2019) - Zheng, Kaikui; Gao, Chenghui; He, Fushan; Jiang, Wei
ABSTRACT: A high-quality brake material was developed by using different rare earth oxide modified resin-based brake materials and designing the composite material through an orthogonal optimization test. The effect of rare earth oxide on the properties of the resin-based brake material, such as the friction and wear, thermal decay resistance, and recovery, was explored using the constant-speed friction test, Chase friction test and worn surface morphological observation. The results show that rare earth lanthanum oxide can be added to improve the friction and wear properties of the brake material compared to cerium oxide and yttrium oxide. At 100–350°C, the friction coefficient of the developed brake material fluctuates in the range of 0.40–0.50, and the material has high friction coefficient, good thermal decay resistance and favourable wear resistance. The friction coefficient of the optimal formulation can reach the GF level, so its tribological properties are very good and better than the brake pads of automobiles at home and abroad.